Tafsir Ekologi dan Relevansinya terhadap Krisis Ekologis di Aceh: Kajian Tafsir Tematik Kontekstual - Widya Kartika Rakhmawati; Safwan Mabrur (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This study aims to examine the concept of ecological Qur’anic exegesis and its relevance to the ecological crisis in Aceh through a contextual thematic (tafsīr maudhū‘ī) approach. The research is motivated by the increasing environmental problems in Aceh, including deforestation, floods, land degradation, and ecosystem destruction, which highlight the need to employ the Qur’anic perspective as an ethical and theological foundation for environmental management. This qualitative library research uses ecological Qur’anic verses as its primary data, analyzed through major Qur’anic commentaries, namely Jāmi‘ al-Bayān by al-Ṭabarī, Tafsīr al-Qur’ān al-'Aẓīm by Ibn Kathīr, Al-Jāmi‘ li Aḥkām al-Qur’ān by al-Qurṭubī, Tafsir Al-Azhar by Hamka, and Tafsir Al-Miṣbāḥ by M. Quraish Shihab. These data are complemented by literature concerning the ecological conditions of Aceh as the contextual framework of analysis. The findings reveal that the Qur’anic ecological paradigm is founded upon the principles of mīzān (balance), the prohibition of fasād (environmental destruction), the avoidance of isrāf (excessive exploitation), and humanity's responsibility as khalīfah to cultivate and preserve the earth (isti‘mār al-arḍ). These principles are highly relevant for explaining both the causes of and solutions to the ecological crisis in Aceh. This study contributes to strengthening the paradigm of ecological Qur’anic exegesis by emphasizing its contextual relevance, thereby providing a conceptual foundation for developing environmentally sustainable policies and ecological awareness based on Qur’anic values.